2014
DOI: 10.2214/ajr.14.12838
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging for Head and Neck Squamous Cell Carcinoma: Quantifying Repeatability to Understand Early Treatment-Induced Change

Abstract: Baseline ADC variability for HNSCC is less than intratreatment ADC change for nodal disease. Assessment of response should consider intrinsic baseline variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
1
28
2
Order By: Relevance
“…A similar observation was made in a recent study with 541 cases of nasopharyngeal carcinoma, showing that a high pretreatment ADC in the primary lesion predicted worse local relapse-free survival and disease-free survival [74]. Hoang et al [75] showed that the treatment-induced early change in ADC (32% ± 31%) of metastatic nodes is significantly different from the baseline variability (8% ± 7%) in the same nodes. These studies showed the feasibility of using DWI as a noninvasive imaging method to monitor treatment response.…”
Section: Treatment Response Monitoring and Predictionsupporting
confidence: 64%
“…A similar observation was made in a recent study with 541 cases of nasopharyngeal carcinoma, showing that a high pretreatment ADC in the primary lesion predicted worse local relapse-free survival and disease-free survival [74]. Hoang et al [75] showed that the treatment-induced early change in ADC (32% ± 31%) of metastatic nodes is significantly different from the baseline variability (8% ± 7%) in the same nodes. These studies showed the feasibility of using DWI as a noninvasive imaging method to monitor treatment response.…”
Section: Treatment Response Monitoring and Predictionsupporting
confidence: 64%
“…Mean ADC values were compared between RT and diagnostic setups in the lesions based on the PET-derived ROIs. A variability or repeatability coefficient was calculated as the SD of ADC percentage change multiplied by 1.96 [38] .…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) has been applied to measure tumor changes to assess the therapy response [ 10 ][ 11 ]. Normally, the apparent diffusion coefficient (ADC) of water molecules within living tissues is derived from diffusion images with an assumption that the water molecular diffusion is a random process [ 12 ].…”
Section: Introductionmentioning
confidence: 99%